Corak Fikih Literalistik-Tekstualistik - Sofyan A. P. Kau (Al-Ulum, 2010)
This paper describes the pattern and characteristics of literal fiqh, jurisprudence that legal opinion can be deduced from the Koran and the hadith texts. Textual understanding is characterized by an emphasis on language analysis. Literal jurisprudence manifests form is evident in the school of Zhahiri with Ibn Hazm as the central scholar. Analytical description of jurisprudence in this paper is compared with substantialrationale base jurisprudence; therefore, the second mode of jurisprudence is seen between the two specifications. One who studies jurisprudence is encouraged to browse and find out where the basic norms or philosophical values, where the norms and the concrete rules that are classified as instruments.